2009
DOI: 10.1016/j.compscitech.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Tension, compression and shear fatigue of a closed cell polymer foam

Abstract: PostprintThis is the accepted version of a paper published in Composites Science And Technology. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination. AbstractA closed cell foam of Polymetacrylimide (Rohacell) with three different densities is studied.The foam is tested quasistatically in tension, compression and shear. The tensile properties scale very well with the relative density of the foam, but the compression and shear properties do not scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 16 publications
2
79
0
Order By: Relevance
“…The present study builds on the work performed in [1] and [2], where only tension fatigue was studied. In [1], tension fatigue experiments were performed on the same materials as used herein, at a load ration R = 0.1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study builds on the work performed in [1] and [2], where only tension fatigue was studied. In [1], tension fatigue experiments were performed on the same materials as used herein, at a load ration R = 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…It was then found that the tensile fatigue data could be normalised this way, enabling the construction of generic, material specific, but density independent, stress-life relations. In a follow-up study [2], the fatigue behaviour in tension, compression and shear of one class of structural foams (Rohacell) was performed. One conclusion from this was that the stress-life relations were different for the different load cases, generally with lower slope for compression and shear, than in tension.…”
Section: Introductionmentioning
confidence: 99%
“…The dashed lines in Fig.2 represent the yield stress in shear for the foam. This is defined by the 0.5% offset stress [8]. There are a few things to notice in Fig.2a.…”
Section: Shear Fatigue Testing Of Core Materialsmentioning
confidence: 99%
“…The model gave excellent agreement with measured crack propagation data and tension-tension fatigue testing results for two closed cell polymer foams, the same two foams used herein. In a subsequent investigation, the fatigue behaviour of Rohacell WF-foams in tension, compression and shear was investigated [8]. It was found that the slope of the stress-life curve was different for different load cases and relative densities.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al have investigated the influence of foam structure on the macroscopic properties of PMI foam [4]. The fatigue behaviors of the PMI foam in tension, compression and shear were investigated by Burman and Zenkert [5][6][7] as well as the impact responses [8][9][10][11]. In addition, the basic mechanical properties of sandwich structures with PMI foam core were also characterized [5,7,[12][13][14][15][16][17][18][19][20][21][22], where the sandwich beams or panels with PMI foam core have been tested in standard or specialized tests such as shearing [7,14,20], three point bending [16,18,20], four point bending [5,12,14], edgewise compression [20,22] and indentation [17,21].…”
Section: Introductionmentioning
confidence: 99%